Effect of Infusion of Calcitonin Gene-Related Peptide on Cluster Headache Attacks: A Randomized Clinical Trial - Vollesen, Anne Luise H; Snoer, Agneta; Beske, Rasmus P; Guo, Song; Hoffmann, Jan; Jensen, Rigmor H; Ashina, Messoud (JAMA neurology, 2018)
Signaling molecule calcitonin gene-related peptide (CGRP) induces migraine attacks and anti-CGRP medications abort and prevent migraine attacks. Whether CGRP provokes cluster headache attacks is unknown. To determine whether CGRP induces cluster headache attacks in episodic cluster headache in active phase, episodic cluster headache in remission phase, and chronic cluster headache. A randomized, double-blind, placebo-controlled, 2-way crossover study set at the Danish Headache Center, Rigshospitalet Glostrup, in Denmark. Analyses were intent to treat. Inclusion took place from December 2015 to April 2017. Inclusion criteria were diagnosis of episodic/chronic cluster headache, patients aged 18 to 65 years, and safe contraception in women. Exclusion criteria were a history of other primary headache (except episodic tension-type headache <5 days/mo), individuals who were pregnant or nursing; cardiovascular, cerebrovascular, or psychiatric disease; and drug misuse. Thirty-seven patients with cluster headaches received intravenous infusion of 1.5 μg/min of CGRP or placebo over 20 minutes on 2 study days. Difference in incidence of cluster headache-like attacks, difference in area under the curve (AUC) for headache intensity scores (0 to 90 minutes), and difference in time to peak headache between CGRP and placebo in the 3 groups. Of 91 patients assessed for eligibility, 32 patients (35.2%) were included in the analysis. The mean (SD) age was 36 (10.7) years (range, 19-60 years), and the mean weight was 78 kg (range, 53-100 kg). Twenty-seven men (84.4%) completed the study. Calcitonin gene-related peptide induced cluster headache attacks in 8 of 9 patients in the active phase (mean, 89%; 95% CI, 63-100) compared with 1 of 9 in the placebo group (mean, 11%; 95% CI, 0-37) (P = .05). In the remission phase, no patients with episodic cluster headaches reported attacks after CGRP or placebo. Calcitonin gene-related peptide-induced attacks occurred in 7 of 14 patients with chronic cluster headaches (mean, 50%; 95% CI, 20-80) compared with none after placebo (P = .02). In patients with episodic active phase, the mean AUC from 0 to 90 minutes for CGRP was 1.903 (95% CI, 0.842-2.965), and the mean AUC from 0 to 90 minutes for the placebo group was 0.343 (95% CI, 0-0.867) (P = .04). In patients with chronic cluster headache, the mean AUC from 0 to 90 minutes for CGRP was 1.214 (95% CI, 0.395-2.033), and the mean AUC from 0 to 90 minutes for the placebo group was 0.036 (95% CI, 0-0.114) (P = .01). In the remission phase, the mean AUC from 0 to 90 minutes for CGRP was 0.187 (95% CI, 0-0.571), and the mean AUC from 0 to 90 minutes for placebo was 0.019 (95% CI, 0-0.062) (P > .99). Calcitonin gene-related peptide provokes cluster headache attacks in active-phase episodic cluster headache and chronic cluster headache but not in remission-phase episodic cluster headache. These results suggest anti-CGRP drugs may be effective in cluster headache management. ClinicalTrials.gov (NCT02466334).